Effectiveness of phonological cues in a picture-naming task in children with cochlear implants and typical hearing - Mieres Maldonado, Daniela; Cambra Vergés, Cristina (Revista de Investigación en Logopedia, 2026)
The use of phonological cues is a widely employed resource in speech and language therapy; however, the outcomes of using this strategy with children with cochlear implants (CIs) have not yet been studied.The aim of this study is to analyse the outcomes of using phonological cues as a lexical access strategy in a group of children with Cis and another with typical hearing (TH).A quantitative observational study was conducted with a sample of 31 children with CIs matched to 31 children with TH, aged between 5 and 7 years, analyzing the phonological cues used by speech-language therapists in response to the children’s naming difficulties. Poisson regression models were applied, controlling for participants’ age and sex.The results indicated that both the CI and TH groups benefited from the use of phonological cues, although the CI group benefited to a lesser extent than the TH group. An older age at the time of implantation was associated with an increase in the number of incorrect answers and non-responses.These findings suggest that phonological cues are a useful tool to support lexical access in picture-naming tasks for the CI group, and they underscore the importance of considering age at the time of implantation when planning speech-language therapy strategies.
Keywords: phonological clues; cochlear implant; intervention strategies; lexical access; picture naming task